Use of monopolar microelectrodes and radiofrequency in the treatment of arytenoid edema after partial horizontal laryngectomy and radiotherapy. Issue 10 (26th July 2021) - Basterra, Jorge; Oishi, Natsuki; López, Isabel; Otero, María; Sánchez, Alvaro; Zapater, Enrique
Abstract: We evaluated the tissue reduction effects using monopolar microelectrodes (MME) coupled to a radiofrequency (RF) generator in arytenoid edema caused by postoperative radiotherapy in larynx. This is a retrospective transversal study, which included 15 patients with supraglottic laryngeal carcinoma. All the patients had undergone a partial horizontal laryngectomy and bilateral neck dissection followed by postoperative radiotherapy. The studied group of patients presented laryngeal stenosis defined by arytenoid edema as a complication, requiring permanent tracheostomy for mean of 12 months. The surgical procedure for treating the edema was the transoral approach of the larynx by microlaryngoscopy under general anesthesia; using 180° MME coupled to a 4‐MHz RF generator delivering 15 W using coagulation mode. A total of 11 (73%) patients were decannulated. The median time for decannulation was 10 weeks. No complications were reported. After 2 years of follow‐ups, no case of re‐stenosis was found. MME coupled to RF is a very efficient method to treat arytenoid edema after adjuvant radiotherapy.